2018
DOI: 10.1039/c7ta11314e
|View full text |Cite
|
Sign up to set email alerts
|

Hole transporting materials based on benzodithiophene and dithienopyrrole cores for efficient perovskite solar cells

Abstract: High efficiency (18.1%) perovskite solar cells are demonstrated by using a hole transporting material with very low reorganization energy (λ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…However, its tedious synthesis and purification is a major obstacle for large‐scale production. To solve this problem and to further study the relationship between HTM structure and device performance, new organic small molecules with appropriate energy levels and favorable hole‐transporting ability were developed to replace spiro‐OMeTAD . The selection of the core structure is of great concern for designing organic small‐molecule‐based HTMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its tedious synthesis and purification is a major obstacle for large‐scale production. To solve this problem and to further study the relationship between HTM structure and device performance, new organic small molecules with appropriate energy levels and favorable hole‐transporting ability were developed to replace spiro‐OMeTAD . The selection of the core structure is of great concern for designing organic small‐molecule‐based HTMs.…”
Section: Introductionmentioning
confidence: 99%
“…To solvet his problem and to furthers tudy the relationship between HTMs tructure and device performance, new organic small molecules with appropriate energy levels andf avorable hole-transporting ability wered evelopedt or eplace spiro-OMeTAD. [16][17][18][19][20][21][22][23] The selection of the core structure is of great concern for designing organic small-molecule-based HTMs. In recenty ears, as eries of HTMs with phenothiazine, [24] acridine, [25] benzo [1,2- [26] truxene, [27] tetraphenylethylene, [28] and others as the core structures were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore,i ti si mperative to develop novel small molecular HTMs to endow PVSCs with higher PCEs free of doping. [7] However,f ully doped PVSCs delivered only aP CE of 18.16 %i nr everse scan and 15.53 %i nf orward scan. [5] In this regard, dithieno[3,2b:2',3'-d]pyrrole (DTP) stands out as an universal electrondonating block that contains heteroatoms of nitrogen (N) and sulfur (S).…”
mentioning
confidence: 99%
“…The devices remained stable when exposed outdoors in Jeddah, Saudia Arabia for a period of consecutive seven days. Furthermore, stable PSC was also reported when the encapsulated device was thermally tested at [80][81][82][83][84][85] C for 90 days. Moisture penetration in hole transporting layer can be restricted by crosslinking the layer.…”
mentioning
confidence: 99%
“…M. K. Nazeeruddin et al 80 have observed and designed two new classes of HTMs based on benzodithiophene (BDT) and dithienopyrrole (DTP) cores. They substituted BDT and DTP central cores with four N,N-bis(4-methoxyphenyl) aniline units through the 2-and 3-positions of thiophene rings giving rise to the tetrakistriphenylamine (TTPA) derivatives.…”
mentioning
confidence: 99%